Analisis Struktur dan Kebahasaan pada Kumpulan Cerita Anekdot serta Rekomendasinya sebagai Modul Ajar Teks Anekdot Tingkat SMA Kelas X Fase E: Analysis of Structure and Linguistic Features in Anecdote Story and Its Recommendation as a Teaching Module for Anecdote Text At High School Class X Phase E - Yudha Sanjaya; Ferina Meliasanti; Dewi Herlina (Transformatika: Jurnal Bahasa, Sastra, dan Pengajarannya, 2026)
This research analyzes the structure and linguistic features of anecdote texts in the book "Kumpulan Cerita Anekdot" (Collection of Anecdote Stories) by Purba et al. with the aim of developing a teaching module based on the Merdeka Curriculum. Using descriptive qualitative methods, the researcher analyzed 20 anecdote stories from 112 available stories. The analysis focused on five structural elements (abstract, orientation, crisis, reaction, and coda) and six linguistic features (past tense sentences, rhetorical sentences, temporal conjunctions, action verbs, imperative sentences, and exclamatory sentences). The research results show that 12 out of 20 anecdote texts meet structural completeness requirements, while 8 texts show varied incompleteness. In terms of linguistic features, none of the 20 texts have completely and perfectly developed linguistic usage. The most striking incompleteness is the use of past tense sentences which are almost absent in most texts. These findings indicate the need for further revision and development so that anecdote texts can meet ideal criteria according to curriculum standards. This research provides practical contributions to Indonesian language teachers in selecting and evaluating teaching materials, as well as for publishers to improve the quality of anecdote text content.